ACT For Life: the development and user engagements of mobile application for prevention and management of psychological distress - Abdul Khaiyom, Jamilah Hanum; Abdul Aziz, Amani Fadzlina; Md. Rosli, Ahmad Nabil; Bahari, Che Amnah; Abdullah, Nur Sakinah Thomas (2023)
Introduction: The COVID-19 pandemic has challenged the ways of modern healthcare delivery, and remote methods of delivering evidence-based mental healthcare are more important now than before (Ho et al., 2020).1 Digital mental health interventions have already been lauded for its ability to reduce cost, transcend physical limits, and increase flexibility and autonomy of users (Wasil et al., 2021) 2, making its use arguably vital in managing the mental health impact of the pandemic. Given that rates of mental disorders are expected to increase post-pandemic (Varma et al., 2021)3, novel methods to introduce preventative and management of mental health issues are needed to reduce the strain on Malaysia’s already overburdened mental healthcare system (Beckstein et al., 2021).4 Objective: The present study elaborated the development and user engagements of ACT for Life, a mobile application of Acceptance and Commitment Therapy (ACT) for prevention and management of psychological distress for Malaysian. Method: The mobile application ACT For Life was developed based on the cloud-based instant messaging i-ACT for Life program that has been tested its effectiveness through a randomized controlled trial.5 The program comprises five weekly modules corresponded to an ACT core processes (Grounding, Unhooking, Acting on Values, Being Kind, and Making Room). The micro-contents were designed in infographic format, 7 interactive exercises and quizzes, 12 audio exercises, and 7 psychoeducation videos. The major improvements from the original program are translation and adaptation into the Malay language. ACT For Life also drops the integrated Islamic spiritual strategies from the original program for multireligious people in Malaysia. The users are encouraged to take Depression, Anxiety, and Stress Scale-21 items (DASS-21) before and after the program. The current mobile application is integrated as part of Selangor Mental Sihat (SEHAT), a comprehensive mental health application involving mental health awareness, literacy, screening, early intervention, and subsidized psychiatric intervention sponsored and managed by one of the state governments in Malaysia. Results: ACT for Life mobile application was live in SEHAT since October 2022 in conjunction with World Mental Health Day. As of February 2023, the number of users for SEHAT and ACT for Life is 17,105 and 726, respectively. Total number of user engagements are follows: Opening of the Program – 724 (99.72%), Week 1 – 446 (61.43%), and Week 2 – 29 (3.99%). None of the users have attended Week 3 modules and above and hence none have completed pre-and post-DASS-21 for analysis of program outcome. Conclusions: The total number of engagements suggests that the ACT for Life mobile application is accessible for the users. In comparison to the similar programme, i-ACT For Life, the number of users for ACT for Life is less. Furthermore, sustainability of user engagements and issue on program completion need to be further studied. Increase promotion of the program, continuous reminders to the users, and therapist-assisted initiative may be the solutions for the issues.